The Influence of Learning Models and Formative Tests on Students Science Learning Outcomes - Misbah Misbah; M. Sidin Ali; Muhammad Arsyad (Postgraduate, University of Mataram, 2025)
Science learning requires learning that is not only centered on the teacher (teacher centered), but must also be centered on students (student centered) (Zulfikar: 2021). This study is a type of true experimental research that aims to determine the effect of learning models and formative tests on the science learning outcomes of students of class VIII of SMPN 3 Majene. The independent variables in this research are the probing prompting and problem-based learning models. The moderator variables are objective and subjective formative tests, while the dependent variable is the learning outcome. The population is all students in class VIII of SMPN 3 Majene at the eight classes. The sample for this research consisted of four classes. The four sample classes are experimental classes with 120 students. Data collection was carried out using science learning outcomes tests. The collected data was analyzed using descriptive and inferential analyses, especially two-way ANOVA analyses. The results of inferential analysis on the hypothesis show that there is influence between the learning model and formative tests on students science learning outcomes